Flacourtia turbinata (Salicaceae: Flacourtieae), a new species from Yunnan, China - Dong, Hongjin; Peng, Hua (Phytotaxa, 2013)
A new species of Flacourtia from Yingjiang, SW Yunnan, China, bordering with Burma, is described and illustrated. Flacourtia turbinata is similar to F. jangomas in leaf and flower shape, but can be easily distinguished for its triplinerved leaf venation, extraordinary long sepals, turbinate fruit and pubescent leaves and twigs when young.